2008
DOI: 10.1002/uog.5816
|View full text |Cite
|
Sign up to set email alerts
|

OP18.07: Assessing correlation between ovarian and stromal volumes and fasting and postprandial insulin levels in PCOS patients

Abstract: Oral poster abstracts However, this is a small group of patients and a larger study is required for adequate statistical analysis. We believe that 3D US is the best available non-invasive technique for assessment of the uterine cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…It is the stromal volume that can be best correlated with fasting insulin levels followed by ovarian volumes and AFC. 25 A similar study has also been done earlier. Study by Pache et al has shown that the degree of insulin resistance can be correlated with ovarian volume and stromal echogenecity.…”
Section: Ov Volume Right Leftsupporting
confidence: 54%
“…It is the stromal volume that can be best correlated with fasting insulin levels followed by ovarian volumes and AFC. 25 A similar study has also been done earlier. Study by Pache et al has shown that the degree of insulin resistance can be correlated with ovarian volume and stromal echogenecity.…”
Section: Ov Volume Right Leftsupporting
confidence: 54%